The Influences of Profitability, Company Growth, Financial Condition, and Debt Default on Going Concern Audit Opinions - Permana, Ghozy Agung; Setyadi, Edi Joko; Fakhruddin, Iwan; Inayati, Nur Isna (Program Studi Akuntansi FPEB UPI, 2024)
This research focuses on property and real estate companies in Indonesia, especially in the context of profitability, company growth, financial condition and debt default on going concern audit opinions. The aim is to evaluate the influence of these factors on going concern disclosures in audit opinions, thereby providing a deeper understanding for stakeholders in assessing the company's financial risk. This research uses secondary data from the annual financial reports of companies listed on the Indonesia Stock Exchange (BEI) during the 2019-2022 period. This research applies logistic regression analysis to test the proposed hypothesis. The results show that profitability and financial condition have a significant negative relationship with going concern as an audit opinion, while company growth and debt default do not show a significant relationship. This emphasizes the importance of financial factors in determining a company's business continuity